Exploring How Emotional Service Experience and Responsiveness Satisfaction Drive Purchase Decisions in a Service Context : JEL Classification: M31, M37, D12, L83, C83 - Permatasari, Dinda Rahma Novita; Hidayat, R. (Newinera Publisher, 2025)
This study aims to explore the influence of emotional service experience and responsiveness satisfaction on purchasing decisions in a service context, using a case study of Mie Gacoan in 2025. This study used a quantitative approach with a survey method, in which 100 Mie Gacoan customer respondents were selected through purposive sampling. Data were collected using a semantic differential scale ranging from 1 to 7 to measure the variables. Validity and reliability tests were conducted to ensure the accuracy and consistency of the instrument. Furthermore, classical assumption tests, multiple linear regression analysis, and significance tests (t-test and F-test) were conducted to test the hypotheses. The results showed that emotional service experience and responsiveness satisfaction had a positive and significant influence on purchasing decisions, both partially and simultaneously. Emotional service experience emerged as a stronger predictor, highlighting the importance of creating a positive emotional impression in service delivery. Responsiveness satisfaction measured through speed, availability, convenience, and empathy also contributed significantly to driving customer purchasing decisions. This study emphasizes that in highly competitive service industries, such as the food and beverage sector, enhancing emotional aspects and responsiveness of service can substantially improve customer purchasing decisions. These findings provide practical implications for service providers to focus not only on product quality, but also on emotional engagement and responsiveness in interactions with customers.